Perilaku Petani Dalam Penggunaan Pupuk Organik Pada Tanaman Padi - Eka Nuari Indarwati; Miftakhul Arifin; Andi Prayoga (Jurnal Penyuluhan Pembangunan, 2024)
AbstractResearch on farmer behavior in using organic fertilizer on rice plants was carried out in Kalitinggar Kidul Village, Padamara District, Purbalingga Regency, from October to December 2022 with the aim of knowing farmer behavior in using organic fertilizer on rice plants. The research was conducted using survey techniques and qualitative descriptive analysis. The determination of the sample locations was carried out purposively with the consideration that Kalitinggar Kidul Village is the village with the lowest rice production in Padamara District, besides that the Kalitinggar Kidul Village area has natural conditions that are very potential for organic rice cultivation. The sample of farmer groups was carried out purposively with the consideration that the two member farmer groups had carried out organic rice cultivation and had cattle, both cows and goats. The population consisted of 128 farmers from two farmer groups, namely the Eko Waluyo Farmer Group with 78 farmers, and Dwi Waluyo with 50 farmers. The number of respondents as a sample of 33 farmers was determined by proportional random sampling from 2 farmer groups. Data collection techniques used in this study using questionnaires, interviews and observations. Data were analyzed by descriptive quantitative. The results showed that 1) the knowledge aspect of farmer behavior in the use of organic fertilizer in lowland rice plants was included in the ignorant category with an achievement score of 77.61%, 2) the attitude aspect of farmer behavior in the use of organic fertilizer in lowland rice plants was included in the agree category with an achievement score of 84.17%, and 3) the skill aspect of farmer behavior in using organic fertilizer in lowland rice plants was included in the unskilled category with an achievement score of 67.92%.